An Assessment of the Feasibility of Phytoextraction for the Stripping of Bioavailable Metals from Contaminated Soils. (30th January 2023) - Santa‐Cruz, Javier; Robinson, Brett; Krutyakov, Yurii A.; Shapoval, Olga A.; Peñaloza, Patricia; Yáñez, Carolina; Neaman, Alexander
Abstract: Phytoextraction has been proposed in many papers as a low‐cost method for remediating contaminated soil. However, if national regulation is based on total metal(loid) concentrations in soil, phytoextraction is generally infeasible because of the long time required for remediation. Assessing phytoextraction requires determination of the dynamic rate of metal removal from soil. Phytoextraction may be feasible if the main goal is to reduce the soluble fraction of the metal(loid) with the goal of reducing bioavailability. However, it has been reported that there is a large mass balance mismatch between the reduction of the soluble metal fraction in contaminated soil and metal uptake by plants. Several studies report that the decrease of soluble fraction of metals in soil is higher than can be accounted for by plant uptake. In other words, studies generally overestimate the feasibility of bioavailable contaminant stripping. Therefore, a more rigorous approach is advisable to ensure that papers on bioavailable contaminant stripping include relevant information on mass balances. Furthermore, to implement the concept of bioavailable contaminant stripping, regulations must distinguish between the bioavailable fraction and the total metal concentration in soil. Environ Toxicol Chem 2023;42:558–565. © 2022 SETAC